ICOS ATC/CAL Flask Release from Svartberget (150.0 m), 2021-06-03–2026-03-01 - Eric Larmanou; Paul Smith; Per Marklund (Integrated Carbon Observation System, 2026)
can contain atmospheric composition data for any of a number of gases; the data can be a mole fraction, isotope ratio, or other related quantity
Larmanou, E., Smith, P., Marklund, P. (2026). ICOS ATC/CAL Flask Release from Svartberget (150.0 m), 2021-06-03–2026-03-01, ICOS RI, https://hdl.handle.net/11676/cfVq2IzDu2tkC2_jVnJPTVaf
Keywords: Atmosphere Thematic Centre; Flask; ICOS; time instant, UTC; time instant, UTC; Δ14C; Δ14C; Δ14C uncertainty; Δ14C uncertainty; number of points; number of points; quality flag; quality flag; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap